Reaction kinetics and reactor performance of recirculated packed bed immobilized enzyme reactor for the synthesis of butyl laurate ... [et al.] / [mikrofilem] - Wong, Tak Hiong; Wu, Hung Yee; Yuzaida Mohd. Yunus; Zaidi Mohd. Noh; Zulkiflee Mohammed Nasir; Zuriani Abdullah (Skudai : Universiti Teknologi Malaysia, 1999)
Project Paper (Bachelor of Chemical Engineering (Bioprocess)) - Universiti Teknologi Malaysia, 1999